EPSPS Gene Amplification Primarily Confers Glyphosate Resistance among Arkansas Palmer amaranth (Amaranthus palmeri) Populations. Issue 3 (26th January 2018) - Singh, Shilpa; Singh, Vijay; Lawton-Rauh, Amy; Bagavathiannan, Muthukumar V.; Roma-Burgos, Nilda
Abstract: Research was conducted to determine whether resistance to glyphosate among Palmer amaranth ( Amaranthus palmeri S. Watson) populations within the U.S. state of Arkansas was due solely to increased EPSPS gene copy number and whether gene copy number is correlated with resistance level to glyphosate. One hundred and fifteen A. palmeri accessions were treated with 840 g ae ha −1 glyphosate. Twenty of these accessions, selected to represent a broad range of responses to glyphosate, underwent further testing. Seven of the accessions were controlled with this dose; the rest were resistant. The effective dose to cause 50% injury (ED50 ) for susceptible accessions ranged from 28 to 207 g ha −1 . The glyphosate-resistant (GR) accessions had ED50 values ranging from 494 to 1, 355 g ha −1, a 3- to 48-fold resistance level compared with the susceptible standard (SS). The 5-enolpyruvylshikimate-3-phosphate synthase ( EPSPS ) gene relative copy number was determined for 20 accessions, 4 plants accession −1 . Resistant plants from five GR accessions (38% of resistant plants tested) did not have increased EPSPS gene copies. Resistant plants from the remaining eight GR accessions (62% of resistant plants tested) had 19 to 224 more EPSPS gene copies than the SS. Among the accessions tested, injury declined 4% with every additional EPSPS copy. ED50 values were directly correlated with EPSPS copy number. The highly resistant accession MIS11-B had an ED50 of 1, 355 g ha −1 and 150 gene copies. Partial sequences of EPSPS from GR accessions without EPSPS amplification did not contain any of the known resistance-conferring mutations. Nearly 40% of GR accessions putatively harbor non–target site resistance mechanisms. Therefore, elevated EPSPS gene copy number is associated with glyphosate resistance among A. palmeri from Arkansas.